2022
DOI: 10.3389/frsc.2022.709968
|View full text |Cite
|
Sign up to set email alerts
|

Recruiting, paying, and evaluating the experiences of civic scientists studying urban park usage during the beginning of the COVID-19 pandemic

Abstract: This paper describes an attempt to utilize paid citizen science in a research project that documented urban park usage during the early stages of the COVID-19 pandemic in two U.S. cities. Strategies used by the research team to recruit, pay, and evaluate the experiences of the 43 citizen scientists are discussed alongside key challenges in contemporary citizen science. A literature review suggests that successful citizen science projects foster diverse and inclusive participation; develop appropriate ways to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…Some argue that financial remuneration of citizen scientists is inappropriate because it could compromise intrinsic motivation to participate. Others contend that non-payment is exploitative, and that appropriate payment values the contributions of citizen scientists, addresses barriers for participation among underserved groups, sustains engagement and improves the quality of data obtained ( Resnik et al , 2015 ; Alizadehtazi et al , 2022 ). Smith et al argue that financial compensation may not be feasible or appropriate for all projects, and that contributions of citizen scientists can be valued through other mechanisms, such as building the knowledge and capacity of citizen scientists, recognition of academic contributions through co-authorship of publications and invitations to speak at conferences ( Smith et al , 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some argue that financial remuneration of citizen scientists is inappropriate because it could compromise intrinsic motivation to participate. Others contend that non-payment is exploitative, and that appropriate payment values the contributions of citizen scientists, addresses barriers for participation among underserved groups, sustains engagement and improves the quality of data obtained ( Resnik et al , 2015 ; Alizadehtazi et al , 2022 ). Smith et al argue that financial compensation may not be feasible or appropriate for all projects, and that contributions of citizen scientists can be valued through other mechanisms, such as building the knowledge and capacity of citizen scientists, recognition of academic contributions through co-authorship of publications and invitations to speak at conferences ( Smith et al , 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] . With the many challenges imposed by the pandemic, which included dramatically reduced recreational opportunities as well as widespread concerns about personal and public health, urban parks, which were one of the few places that urban dwellers were allowed to visit outside their homes, became important destinations.In order to understand the role of parks during the COVID-19 pandemic, a variety of data and methods have been used by researchers to conduct relevant studies: including carrying out field surveys 10,13,14 , recruiting civic scientists to make observations 15,16 , collecting geotagged data from social media [17][18][19][20] , and acquiring data from recreational tracking apps 21 . Decreased visits to urban greenspaces in central London was reported 20 , which could be attributed with working from home restrictions; similarly, in a study conducted in multiple cities across North Carolina, 56% of survey respondents indicated that they had ceased or reduced their use of parks, with geotracked park visits dropping by 15% 14 .…”
mentioning
confidence: 99%